Stem Cells in Clinical Practice and Tissue Engineering - Sharma, Rakesh (IntechOpen, 2018)
Stem Cells in Clinical Practice and Tissue Engineering is a concise book on applied methods of stem cell differentiation and optimization using tissue engineering methods. These methods offer immediate use in clinical regenerative medicine. The present volume will serve the purpose of applied stem cell differentiation optimization methods in clinical research projects, as well as be useful to relatively experienced stem cell scientists and clinicians who might wish to develop their stem cell clinical centers or research labs further. Chapters are arranged in the order of basic concepts of stem cell differentiation, clinical applications of pluripotent stem cells in skin, cardiac, bone, dental, obesity centers, followed by tissue engineering, new materials used, and overall evaluation with their permitted legal status.